Using interactive technology in visualized narration book as a medium to promote hakka blue-dyed in jhanghu community. Issue 1 (March 2021) - Peng, L H; Lin, Y H; Siswanto, I
Abstract: Looking at many products that combine indigo dyeing on the market, the old and new products are continually being introduced. However, there are only a handful of picture books related to traditional craftsmanship and manufacturing. In the literature discussion, we also found that the blue dyeing method was once replaced by modern industrial technology due to the complicated process. In recent years, with the evolution of the times, the awareness of environmental protection has risen, and the advantages of natural environmental protection of indigo dyeing have become increasingly prominent. From plant harvesting, refining indigo to dyeing, no chemical dyes are added. Therefore, let the traditional indigo dyeing technique, which has been in decline for a long time, eliminate the conventional impression and reappear in life with different product appearances. In this regard, the team uses three-dimensional and interactive technology application teaching picture books to allow the public to record the blue dye production process with a flexible, exciting, and plot-style story structure, and a more effective and easily acceptable way of learning technology for young people Ability to absorb relevant knowledge. Besides, in the future, we hope to use this kind of picture book framework to collect, record and preserve Taiwan's unique traditional techniques in picture books and animation videos.